Analysis of Transactional Leadership and Organizational Communication on Employee Performance with Job Satisfaction as A Mediating Variable at The Medan Plantation Seed and Protection Center Plantation Crops In Medan - Demensah Ginting; Mesra B; Kiki Farida Ferine (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is a strategic factor in supporting the success of government technical agencies, particularly the Medan Plantation Seed and Plant Protection Center (BBPPTP), which plays an important role in quality testing, seed certification, and plantation plant protection. This study aims to analyze the effect of transactional leadership and organizational communication on employee performance with job satisfaction as a mediating variable. The study used a quantitative approach with a census method of 135 civil servants at BBPPTP Medan. Primary data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results showed that transactional leadership and organizational communication had a positive and significant effect on employee performance and job satisfaction. Job satisfaction also has a positive and significant effect on employee performance and is proven to mediate the influence of transactional leadership and organizational communication on employee performance. These findings indicate that the consistent application of transactional leadership, effective organizational communication, and increased job satisfaction are important factors in improving the performance of BBPPTP Medan employees. This study is expected to provide empirical contributions to the development of human resource management theory in the public sector and serve as practical considerations for the management of BBPPTP Medan in formulating policies to improve employee performance.